2016
DOI: 10.1038/nrc.2015.18
|View full text |Cite
|
Sign up to set email alerts
|

The kinome 'at large' in cancer

Abstract: Over the past decade, rapid advances in genomics, proteomics and functional genomics technologies that enable in-depth interrogation of cancer genomes and proteomes and high-throughput analysis of gene function have enabled characterization of the kinome 'at large' in human cancers, providing crucial insights into how members of the protein kinase superfamily are dysregulated in malignancy, the context-dependent functional role of specific kinases in cancer and how kinome remodelling modulates sensitivity to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
229
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 241 publications
(231 citation statements)
references
References 130 publications
1
229
0
1
Order By: Relevance
“…However, protein kinases exert pleiotropic functions, such as increased survival, progression of the cell cycle, differentiation, adherence, or migration, that are dependent on the tissue and molecular environment of the cells. Ultimately, this implies a context-dependent functional role of specific kinases in cancer, i.e., oncogene or TSG function (53). Our data provide an additional example of a tyrosine kinase that acts as a tumor suppressor.…”
Section: V600ementioning
confidence: 88%
“…However, protein kinases exert pleiotropic functions, such as increased survival, progression of the cell cycle, differentiation, adherence, or migration, that are dependent on the tissue and molecular environment of the cells. Ultimately, this implies a context-dependent functional role of specific kinases in cancer, i.e., oncogene or TSG function (53). Our data provide an additional example of a tyrosine kinase that acts as a tumor suppressor.…”
Section: V600ementioning
confidence: 88%
“…2C). Importantly, these aberrant ALK proteins in Aska-SS were detected using (14). C, ALK expression and phosphorylation in SS cell lines.…”
Section: Alk Represents a Novel Driver In Ssmentioning
confidence: 99%
“…Next, tyrosine kinases (TK) were extracted from the original dataset, as these represent an important class of oncogenes and druggable targets (14). This resulted in the identification of 132 phosphotyrosine peptides belonging to 41 TKs, including 26 receptor tyrosine kinases (RTK) and 15 nonreceptor TKs (Supplementary Table S4).…”
Section: Phosphotyrosine Profiling Of Human Sarcoma Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not imply that screening centers have focused on the same molecular targets of approved drugs. For instance, recent genomic studies identified 91 protein kinases as "cancer drivers," only 22% of which are targeted by FDA-approved therapies (Fleuren et al, 2016). Indeed a substantial focus by screening centers on the primary target class, transferase, is apparent, and kinases represent the majority of targets in that class (Table 2).…”
Section: The Impact Of Screening Centers In Cancermentioning
confidence: 99%